Legal form
1 online resource.
Keywords: "A century after the publication of Evgeny Pashukanis's pivotal book General Theory of Law and Marxism, this collection presents a comprehensive account and analysis of his key concept of legal form. Evgeny Pashukanis's General Theory, born amidst the fervour of the first socialist revolution, remains still a crucial reference point in Marxist theories of the law and critical legal theory. Its theoretical depth paved the way for new understandings of the relationship between Marxism and the law. Its crucial virtue continues to be, even after a century, the ability to articulate epochal concerns in the context of a socialist revolution that turned hitherto theoretical problems into dilemmas of practice. This book returns to Pashukanis's main concept: 'legal form'. Through this jurisprudential category Pashukanis aimed to grasp the dependence of the law on the economy, and at the same time, to enquire into the degree to which the law preserves its autonomy from economic relations. In other words, the legal form as a concept conveys both the law's dependence on the economic sphere of exchange and its greatest inherent specificity: the way it translates economic relations into its proper language and set of legal/ideological constructs. The contributions to this volume provide a range of perspectives on how the concept of legal form has been developed and reinterpreted. Including the first English translation of Pashukanis's essay, 'Hegel, State and Law', this collection will be of considerable interest to scholars and students of legal and political theory"--